2002
DOI: 10.1111/j.1574-6968.2002.tb11214.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction and intergeneric conjugative transfer of a pSG5-based cosmid vector fromEscherichia colito the polyisoprene rubber degrading strainMicromonospora aurantiacaW2b

Abstract: A non-rubber degrading mutant of the polyisoprene rubber degrading bacterium Micromonospora aurantiaca W2b lacking the capability to form halos on latex overlay agar plates was isolated after N-methyl-N-nitro-N-nitrosoguanidine mutagenesis. A 10.3-kb shuttle cosmid vector pGM446 was constructed from the Streptomyces cloning vectors pGM160 and pOJ446. This vector was transferred by conjugation from Escherichia coli to M. aurantiaca W2b. The frequency of formation of exconjugants with pGM446 was 3.6 x 10(-3). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Members of the second group show weaker growth in submers culture but grow and form clear zones on NR latex-overlay agar plates. These bacteria belong to streptomycetes and related genera. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Members of the second group show weaker growth in submers culture but grow and form clear zones on NR latex-overlay agar plates. These bacteria belong to streptomycetes and related genera. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The devulcanization process of rubber involves the breaking of the multiple C-S bonds along with the polymeric chains, where removing sulfur makes the recycling of rubber easier. Aerobic and anaerobic microorganisms are being intensively studied as devulcanization prompters, where the metabolic pathways and the enzymes involved, are becoming better known 2426 . The presence of actinomycetes to metabolize purified natural rubber as the only source of carbon has already been described since 1995, when Heisey and Papadatos, based on fatty acid profiles and cell walls showing seven strains of Streptomyces , two of Amycolatopsis and one of Nocardia , the authors further concluded that actinomycetes were the major organisms involved in the biodegradation of natural rubber hydrocarbons 27 .…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria belong to Streptomycetes and related genera [46,47] . From the several microorganisms isolated and tested Actinomycetes showed the ability to degrade NR and to use it as carbon source [48] . Both Nocardia strain [34] and Xanthomonas strain [35] led to accumulation of oligomers with molar mass around 100 g/mol.…”
Section: Biodegradationmentioning
confidence: 99%
“…Numerous publications, as for example [21,[25][26][27][28][29][30][31][32][33][34][35][41][42][43][44][45][46][47][48][49][50][51][52][53][54] , are devoted to oxidative methods of degradation natural rubber. The widely used approach is degradation through the epoxidation reaction of isoprene units of the rubber polymer chain.…”
Section: Chemical Degradationmentioning
confidence: 99%